Role of complement C5a and histones in septic cardiomyopathy - Fattahi, Fatemeh; Frydrych, Lynn M.; Bian, Guowu; Kalbitz, Miriam; Herron, Todd J.; Malan, Elizabeth A.; Delano, Matthew J.; Ward, Peter A. (Molecular Immunology, 2018)
Polymicrobial sepsis (after cecal ligation and puncture, CLP) causes robust complement activation with release of C5a. Many adverse events develop thereafter and will be discussed in this review article. Activation of complement system results in generation of C5a which interacts with its receptors (C5aR1, C5aR2). This leads to a series of harmful events, some of which are connected to the cardiomyopathy of sepsis, resulting in defective action potentials in cardiomyocytes (CMs), activation of the NLRP3 inflammasome in CMs and the appearance of extracellular histones, likely arising from activated neutrophils which form neutrophil extracellular traps (NETs). These events are associated with activation of mitogen-activated protein kinases (MAPKs) in CMs. The ensuing release of histones results in defective action potentials in CMs and reduced levels of [Ca 2+ ]i-regulatory enzymes including sarco/endoplasmic reticulum Ca 2+ -ATPase (SERCA2) and Na + /Ca 2+ exchanger (NCX) as well as Na + /K + -ATPase in CMs. There is also evidence that CLP causes release of IL-1β via activation of the NLRP3 inflammasome in CMs of septic hearts or in CMs incubated in vitro with C5a. Many of these events occur after in vivo or in vitro contact of CMs with histones. Together, these data emphasize the role of complement (C5a) and C5a receptors (C5aR1, C5aR2), as well as extracellular histones in events that lead to cardiac dysfunction of sepsis (septic cardiomyopathy).
CRIS-Team Scopus Importer:2020-12-21
Keywords: Cecal ligation and puncture (CLP); Intracellular calcium ([Ca; Na+/Ca; Na+/K+-ATPase; NLRP3 inflammasome; Sarco/endoplasmic reticulum Ca